Phytosynthesized Nanoparticles as Novel Antifungal Agent for Sustainable Agriculture: A Mechanistic Approach, Current Advances, and Future Directions - Javeria Parveen; Tahira Sultana; Abeer Kazmi; Khafsa Malik; Abd Ullah; Amir Ali; Bushra Qayyum; Naveed Iqbal Raja; Zia-ur-Rehman Mashwani; Saif Ur Rehman (Journal of Nanotechnology)
Due to rapidly changing environmental conditions, virulent pathogens have arisen continuously that invades the crops and badly affects their yield and quality of the cash crops which results in economic losses. To overcome the prevalent infection of fungal pathogens, there is an utmost need to develop alternative techniques that avoid conventional agriculture practices. The use of various chemical fungicides is not an environmentally sustainable solution to fungal diseases because it produces environmental contamination and is dangerous for human health. Nanotechnology provides solutions to disease control issues in a significant way. The scientific and industrial systems are being changed by this development. Similarly, nano-based instruments are highly promising in the agriculture sector, particularly for the production of powerful formulations that require appropriate distribution of agrochemicals, nutrients, pesticides/insecticides, and even growth regulators for improved efficiency of use. Nanotechnology provides an inexpensive, environmentally friendly, and alternative effective monitoring of agricultural fungal pathogens. Green nanotechnology is an innovative methodology that revolutionized the field of agriculture to solve these problems. Despite increasing plant growth, nanoparticles meet the agriculture demand for high yield. This study mainly focuses on the promise of various methods for the treatment of fungal diseases through nanoparticles.